PENGARUH WORKING CAPITAL TURNOVER DAN TOTAL ASSETS TURNOVER TERHADAP RETURN ON ASSETS PADA PT INDOCEMENT TUNGGAL PRAKASA TBK PERIODE 2013 – 2023 - Rizki Pratama Hasibuan; Lisdawati (Journal of Research and Publication Innovation, 2025)
This study aims to analyze the influence of Working Capital Turnover (WCTO) and Total Assets Turnover (TATO) on Return on Assets (ROA) at PT. Indocement Tunggal Prakarsa Tbk during the period 2013-2023. The data used is secondary data obtained from the company's annual financial statements published on the Indonesia Stock Exchange. The research method used is a quantitative method with an associative approach. The data analysis technique used is multiple linear regression analysis. The results of the study show that WCTO has no significant effect on ROA, as evidenced by the t-statistic value (-1.633) < t-table (2.262) with a significance level of 0.141 > 0.05 and a correlation coefficient test value of 0.788. TATO has a positive and significant effect on ROA, as evidenced by a significance level of 0.010 < 0.05 and the calculation results show that the t-statistic (3.356) > t-table (2.262) and the correlation coefficient test value is 0.788. Simultaneously, both WCTO and TATO have a significant effect on ROA, as can be seen from the significance level of 0.021 < 0.05 and the calculated F-statistic (6.562) > F-table (4.46), as well as a coefficient of determination value of 62.1% and the remaining 37.9% is influenced by other variables not included in this study. These findings indicate that asset utilization efficiency and working capital turnover speed play an important role in improving company profitability.